Pengaruh Motivasi Berprestasi dan Gaya Mengajar Guru Terhadap Prestasi Belajar Dalam Pembelajaran Ekonomi - Dina Aulia; Dessi Susanti (Universitas Negeri Padang, 2022)
This study aims to determine the effect of achievement motivation and teacher teaching style on learning achievement, determine the effect of achievement motivation on learning achievement, and determine the effect of teacher teaching style on learning achievement. The sample of this study were 92 students of class XI IPS SMAN 2 Pariaman. data collection using questionnaires and documentation. The data analysis technique used multiple regression analysis, f test, t test and R2. Based on the hypothesis t test, it can be concluded that there is a significant effect between achievement motivation and teacher teaching style on learning achievement. there is an influence of achievement motivation on learning achievement and there is an influence of teacher teaching style on student achievement. The variable of achievement motivation and teaching style of teachers has an influence of 51%, while 49% is influenced by other variables. Keywords : achievement motivation, teacher teaching style